2008
DOI: 10.1158/1055-9965.epi-07-2680
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Steroid Hormone Biosynthesis Genes and Risk of Breast Cancer and Fibrocystic Breast Conditions in Chinese Women

Abstract: Common variants in genes encoding for key enzymes involved in steroidogenesis may alter sex steroid hormone levels, thereby influencing susceptibility to breast carcinoma and related conditions. In a casecontrol study of Chinese women, we examined genotypes of the CYP11A1 pentanucleotide [(TAAAA) n ] repeat (D15S520), CYP17A1 rs743572, and HSD17B1 rs605059 polymorphisms in relation to the risk of breast cancer and fibrocystic breast conditions, comparing 615 women with breast cancer and 467 women with fibrocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…First, 11 publications were collected by searching the databases [6][7][8][9][10][11][12][13][14][15][16]. Second, one study [8] included a portion of the previously published data from the Harvard Nurse's Health Study [15] and the Hawaii-Los Angeles Multiethnic Cohort [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, 11 publications were collected by searching the databases [6][7][8][9][10][11][12][13][14][15][16]. Second, one study [8] included a portion of the previously published data from the Harvard Nurse's Health Study [15] and the Hawaii-Los Angeles Multiethnic Cohort [16].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HSD17B1, which encodes the 17HSD type 1 enzyme that catalyzes the final step of estradiol biosynthesis, may play a significant role in breast cancer development [16]. A common polymorphism (Ser312Gly) of HSD17B1 had been examined in relationship to breast cancer risk in 11 studies with inconclusive results [6][7][8][9][10][11][12][13][14][15][16]. Although current evidence indicated that HSD17B1 Ser312Gly polymorphism may not affect either the catalytic or the immunological properties of the enzyme [20], some studies on cancer epidemiology suggested that Ser allele may be a significantly increased risk for breast cancer [7,8,9,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Caucasian and Asian population reported an association of 4 and 6 repeat alleles correspondingly with that of PCOS [18]. Further, (tttta) 6 allele was shown to be linked with breast cancer and prostate cancer in Chinese and Slovanian population respectively [9,25]. Daneshmand et al, (2002) observed an over-representation of 9 repeat allele in PCOS patients.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the importance of 17HSD1 in breast cancer, few epidemiologic studies concerning HSD17B1 and breast cancer have been conducted [21][22][23][24][25]. The largest study was reported by Feigelson et al [25] that investigated 5370 breast cancer cases and 7480 matched normal controls.…”
Section: Hsd1mentioning
confidence: 99%